2000
DOI: 10.1021/jp000035l
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation on the Adsorption Properties of Precious Metal Clusters toward NO:  A Density Functional Study

Abstract: The adsorption properties of precious metal clusters such as Rh, Pd, Ag, Ir, Pt, and Au toward NO were systematically investigated using the density functional calculations. It was found that the most energetically stable adsorption state of NO on the tetrahedral M 4 clusters was found to be the NO/Ir 4 system. The ability of the precious metal clusters to activate the N-O bond was also discussed mainly from a geometric point of view. The entire linear behavior of the elongation of the N-O bond of NO molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
(74 reference statements)
4
23
0
Order By: Relevance
“…The AuAN bond length is 2.27 Å and the stretching frequency is 310.9 cm 21 . This is similar to ammonia adsorption on Au 20 , in which NH 3 interacts via the N atom at the apex site of Au 20 and the adsorption energy is 11.70 kcal/mol and the AuAN bond length is 2.349 Å . [53] This is in accordance with the result that the anchoring AuAN interaction is dominant for gold clusters and is stronger for larger gold clusters.…”
Section: Molecular Adsorption Via N Atomsupporting
confidence: 56%
See 1 more Smart Citation
“…The AuAN bond length is 2.27 Å and the stretching frequency is 310.9 cm 21 . This is similar to ammonia adsorption on Au 20 , in which NH 3 interacts via the N atom at the apex site of Au 20 and the adsorption energy is 11.70 kcal/mol and the AuAN bond length is 2.349 Å . [53] This is in accordance with the result that the anchoring AuAN interaction is dominant for gold clusters and is stronger for larger gold clusters.…”
Section: Molecular Adsorption Via N Atomsupporting
confidence: 56%
“…[28][29][30][31][32][33] Although impressive progress has been achieved in understanding the adsorption of small molecules on small gold clusters, computational studies for large gold clusters are generally lacking. A notable exception is the study of Gao et al [34] which examined the adsorption of CO on free subnanometer gold clusters (Au 16 -Au 18 , Au 20 , and Au 27 -Au 35 ).…”
Section: Previous Calculations For Adsorption Of Small Molecules On Gmentioning
confidence: 99%
“…The lowest-energy configuration found by us corresponds to a tetrahedron with a spin multiplicity of 7; this is in agreement with one set of earlier calculations. 25 We find two energetically degenerate isomers that lie higher than this by an amount of 0.05 eV/atom: a square geometry with a spin multiplicity of 5, and a non-magnetic tetrahedron. We note that some previous studies 7, 21,23 have claimed that the latter configuration corresponds to the lowest-energy isomer.…”
Section: Resultsmentioning
confidence: 77%
“…The group 8-10 precious metals (Ru, Rh, Pd, Os, Ir, Pt) are well known as effective catalysts in chemical and automobile industries [1][2][3][4][5]. It has been found that small clusters of these metals are better catalysts with a strong dependence on the cluster size [1,2].…”
Section: Introductionmentioning
confidence: 99%